THE ESTABLISHMENT OF THE SHARĪᶜAH ADVISORY COUNCIL OF CENTRAL BANK OF MALAYSIA: SPECIAL REFERENCE TO SECTION 51 OF CENTRAL BANK OF MALAYSIA ACT 2009 (ACT 701) - Mohammad Azam Hussain (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Sharīᶜah Advisory Council which established under the aegis of the Central Bank of Malaysia (CBM), is designated as the highest authoritative body for the ascertainment of Sharīᶜah ruling in the matters of Islamic financial business. This apex advisory council is currently regulated by the Central Bank of Malaysia Act 2009. Hence the establishment of this council is pursuant to the statutory requirement. This article seeks to analyse the statutory requirement of Section 51 pertaining to the establishment of the Sharīᶜah Advisory Council of Central Bank of Malaysia. This is doctrinal legal research with the qualitative method. The primary data of statutory provisions were scrutinized by using the method of content analysis. The study found that there are several deficiencies of the provision in dealing with the establishment of Sharīᶜah Advisory Council pertaining to the legal interpretation, the legal basis for the establishment of Sharīᶜah Advisory Council, the procedures to be adopted and the position of the Sharīᶜah Advisory Council within Central Bank of Malaysia’s Organization Structure. Finally, the article suggests several amendments be made by respective authorities in order to strengthen the legal aspect of the establishment of Sharīᶜah Advisory Council of Central Bank of Malaysia.